Effects of curvature radius on flexible eddy current array sensors for the curved surface of metal components - Deng, Zhiyang; Li, Danyu; Qi, Pan; Shao, Wenbin; Chen, Tao; Song, Xiaochun; Kang, Yihua (Frontiers in Physics, 2022)
Flexible eddy current array sensor owns the advantages of high sensitivity and strong adaptability but the results are always affected by the curvature radius of complex curved surfaces. The relationship between the curvature radius of curved surface and detection signals for surface-breaking cracks is mainly discussed. The change of magnetic field caused by curved surface in present eddy current testing is specially pointed out, which manifest themselves in the compression or enhancement of the testing signal in its peak value and the baseline drifts. The simulation and experiment results indicate that the concave surface weakens the signal while the convex surface enhances the signal. The signal amplitude decreases with the decrease of the curvature radius for the concave surface while it is the opposite for the convex surface. Meanwhile, the coil spacing significantly affects the amplitude-curvature radius curve. Furthermore, the fluctuation characteristic affected by curvature radius under different coil spacing is analyzed. The discovery and results will benefit the quantitative evaluation of the flexible eddy current array testing.